Controller Design for Distributed Secondary Voltage Restoration in the Islanded Microgrid - Feng, Yiwei; Ma, Jing (Frontiers in Energy Research, 2022)
The extensive usage of the cyber communication system in multiple distributed secondary controls of islanded microgrids (MGs) suggests that the effects of the communication network and security concerns on system stability cannot be negligible. This study proposes a distributed fault-tolerant secondary voltage recovery method for multiple distributed generators (DGs) in the MGs of islanded mode based on a sliding mode surface. Compared to the traditional asymptotically convergent distributed control method, the proposed controller quickly eliminates the voltage deviation caused by the primary control and provides power sharing in the presence of external disturbance and actuator fault, which can regulate the average voltage magnitude of all the DGs to an expected value. The effectiveness of the proposed strategy is verified by the simulation studies conducted in the MATLAB/Simulink platform.